Efficacy of Prolonged Speech Therapy in Persons with Stuttering: Perceptual Measures - Santhosh M; Savithri S.R. (Journal of All India Institute of Speech and Hearing, 2007)
Over centuries clinicians and researchers have offered different approaches to stuttering treatment. Among these prolonged speech has yielded the greatest effectiveness and appeared to be the strongest treatment in both the long- and short-term evaluations. However several concerns have been expressed with respect to type of outcome measures used and post-therapy unnaturalness sounding speech. The aim was to investigate the efficacy of prolonged speech therapy in persons with stuttering. Thirty persons with stuttering participated in the present study. A 300-word standard reading passage in Kannada, spontaneous speech/conversation was recorded before, after, and 6-month after prolonged speech therapy. Percent dysfluency, rate of reading and mean naturalness scores (MNS) were measured. Results indicated significant reduction in percent dysfluency and increase in MNS was noticed in the post therapy condition. However, percent dysfluency increased significantly in 6-month post therapy condition.